’Inquiry Physics’ Program for Students-Implementation of Inquiry Learning in the Physics Lessons in the High School in Israel - Sigron, Michal (Wydawnictwo Naukowe UAM, 2017)
Teaching of the Sciences recently emphasizes more than in the past the importance of the student’s experience in inquiry, in different places in the world in general and in Israel in particular. This article describes the process of scientific inquiry and the change of the perception of the role, both of the student and of the traditional teacher, in the performance of the inquiry process. The article presents different initiatives that integrate the learning of inquiry in the teaching of physics in the high school in Israel. These initiatives show that the inquiry laboratories have the potential to promote meaningful learning among the students, to increase the depth of their understanding of the scientific concepts and the understanding of the nature of science. The article focuses on ‘Inquiry Physics’ program for students and presents the goals, the target audience, the time framework, and the structure of this program. The program aims to assemble the different initiatives under one framework and to provide them with an appropriate place in the teaching of physics. The learning method of inquiry is now fledgling in the State of Israel and mainly in the knowledge realm of physics. Therefore, exposure to this program may contribute to the body of knowledge on the characteristics of learning and teaching through inquiry in general and on the teaching of physics in particular.
Program nauczania fizyki oparty na samodzielnych poszukiwaniach jako przykład tego rodzaju nauczania w izraelskiej szkole średniej
Keywords: inquiry learning; physics inquiry